Increasing systemic legal risks in the EU: The economic impacts of changes to the EU's Product Liability legislation - Matthias Bauer; Elena Sisto (European Centre for International Political Economy (ECIPE), 2023)
The EU's Product Liability Directive (PLD) determines the rules for strict product liability in the EU. It establishes a framework in which manufacturers' liability is determined solely based on the presence of defects in the product, regardless of the manufacturer's fault. The PLD is intended to serve as a "safety net" when fault-based or contractual liability rules do not offer sufficient compensation to consumers. It operates independently from contractual arrangements between businesses and consumers, and it cannot be weakened by contractual agreements between businesses and consumers. The PLD is a horizontal regulation that applies to a wide range of industries in the EU because it applies to all products available on the EU market. The recently proposed changes by the European Commission would increase systemic legal uncertainty for producers and sellers of technology-intensive goods and services in the EU. The impact assessment of the European Commission does not sufficiently account for changes to the PLD proposed in 2022. Nor does it sufficiently account for the major impacts of increased legal uncertainty for European businesses. Legislators in the Council and the European Parliament should slow negotiations to allow time for policymakers to collect more evidence on the impacts on businesses, insurers, and courts we detail in this paper. This would be an opportunity to improve regulatory quality in light of the high levels of legal uncertainty associated with the changes proposed by the Commission.
Keywords: 330; Product liability; EU countries; Produkthaftung; EU-Staaten